Volunteering Activity during Pandemic: Challenge and Involvement from UUM Students - Nurnazihah Basirun,; Sharima Ruwaida Abbas,; Rohani Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has presented unprecedented global challenges impacting students' volunteering activities. This paper highlights the factors, challenges, and advantages of volunteering for Universiti Utara Malaysia (UUM) students during the pandemic. The study explores students' experiences and contributions to volunteering factors. The questionnaires were distributed to 103 university students online using quantitative methods. The findings highlight the internal factors influencing students' involvement in volunteering during COVID-19: self-enhancements, social, interpersonal, and career. In contrast, the external factors were peer influence, recognition from society, feeling responsible for society, additional income, free time, and gaining experience. Furthermore, the questionnaire results show that students face challenges carrying out volunteer activities during COVID-19. Lastly, the findings highlight the advantage gained by doing this volunteer activity. These aim to inspire further engagement, research, and recognition of volunteers' vital role in combating the pandemic and building resilient communities by examining the experiences and impact of UUM student volunteers.